2019
DOI: 10.1186/s12917-019-2010-x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma affects the proliferation of canine bone marrow-derived mesenchymal stromal cells in vitro

Abstract: Background Reported efficacy of platelet-rich plasma (PRP) in regenerative medicine is contradictory. We validated the effects of PRP on proliferation of canine bone marrow-derived multipotent mesenchymal stromal cells (K9BMMSCs) in vitro. PRP was extracted from blood of six dogs with osteoarthritis. K9BMMSCs were established from bone marrow and characterized for CD90 and CD19 expression by immunocytochemistry. Effects of PRP concentrations on viability of matching autologous K9BMMSCs were valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In the following treatment period, the syringes with the medium of one array were switched to medium containing 10% human blood serum. In vitro cultivation of adult human stem cells with human blood plasma or serum has demonstrated increased proliferation and viability [ 14 , 15 , 16 , 17 ]. To investigate a potential effect of human serum on hCSC migration, we tracked the covered path of single cells that were cultivated under exposure to blood serum or to control medium in our microfluidic device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following treatment period, the syringes with the medium of one array were switched to medium containing 10% human blood serum. In vitro cultivation of adult human stem cells with human blood plasma or serum has demonstrated increased proliferation and viability [ 14 , 15 , 16 , 17 ]. To investigate a potential effect of human serum on hCSC migration, we tracked the covered path of single cells that were cultivated under exposure to blood serum or to control medium in our microfluidic device.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the use of convalescent plasma is currently under discussion as a treatment option in the COVID-19 pandemic [ 12 , 13 ]. In vitro cultivation of adult human stem cells with human blood plasma or serum has demonstrated increased proliferation and viability [ 14 , 15 , 16 , 17 ]. Mishima and coworkers showed increased migration of human articular chondrocytes and mesenchymal stem cells (MSCs) in response to 5, 10 and 20% fetal bovine serum (FBS) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Isolated hCSCs were able to grow clonally while maintaining their capability of sphere formation and differentiated efficiently into α-actinin + cardiomyocyte-like cells. Although the application of human blood serum, blood plasma or platelet-rich plasma on stem cell cultures has already been shown to effectively promote cell proliferation [21,22,[49][50][51][52][53], the cardiovascular system and especially cardiac stem cells have not been investigated so far. Within this study we likewise could demonstrate an overall enhancing effect of human blood serum on adult human cardiac stem cells, while no age dependency could be detected in terms of proliferation and metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The osteogenic experiments showed that PRP induced significantly greater mineralization of hDPCs. Some recent studies have developed culture conditions for in vitro expansion of cells treated by PRP ( Lucarelli et al, 2003 ; Yeom et al, 2016 ; Pandey et al, 2019 ; Hahn et al, 2020 ). These research articles also focused on optimizing concentrations of PRP used for treatments ( Lucarelli et al, 2003 ; Pandey et al, 2019 ; Wang et al, 2019 ; Hahn et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have developed culture conditions for in vitro expansion of cells treated by PRP ( Lucarelli et al, 2003 ; Yeom et al, 2016 ; Pandey et al, 2019 ; Hahn et al, 2020 ). These research articles also focused on optimizing concentrations of PRP used for treatments ( Lucarelli et al, 2003 ; Pandey et al, 2019 ; Wang et al, 2019 ; Hahn et al, 2020 ). Pandey et al reported that 2.5–20% PRP (v/v) concentrations promoted cell migration and proliferation in vitro , while 40% PRP suppressed their migration and proliferation ( Pandey et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%